2001
DOI: 10.1111/j.1745-4522.2001.tb00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Frying Medium During Deep‐frying of Food Rich in Proteins and Carbohydrates

Abstract: Changes in the f j i n g medium (rapeseed oil) during controlled deep-frying of slicedpotatoes and codfillets and oil heated without them were compared. Fifteen f j i n g cycles were conducted each day for five days. Results showed that oil after f j i n g of cod fillets contained 10% less triacylglycerol (TAG) polymers and 40% less TAG dimers than other oils. Other parameters (iodine and anisidine values and absolption value at 233nm) showed that less thennooxidative products formed duringfjling of food rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 10 publications
5
42
0
Order By: Relevance
“…Changes in the absorption of 1% solutions of analyzed samples of fat (E 1% 1cm ) at λ5233 and 270 nm determine the content of secondary oxidation products in fats, especially those containing aldehydes and ketones (Tynek et al, 2001). Data contained in Table 5 indicate relatively small changes, which confirm previous conclusions on changes in fatty acids in the tested samples subjected to heating.…”
Section: Determination Of the Absorption Level Of 1% And 10% Solutionsupporting
confidence: 77%
See 4 more Smart Citations
“…Changes in the absorption of 1% solutions of analyzed samples of fat (E 1% 1cm ) at λ5233 and 270 nm determine the content of secondary oxidation products in fats, especially those containing aldehydes and ketones (Tynek et al, 2001). Data contained in Table 5 indicate relatively small changes, which confirm previous conclusions on changes in fatty acids in the tested samples subjected to heating.…”
Section: Determination Of the Absorption Level Of 1% And 10% Solutionsupporting
confidence: 77%
“…It may also be the antioxidant effects of products formed during the heating of biological material, e.g. as a result of the Maillard reaction (Tynek et al, 2001) For other variants of roasting the Pv was found to be in the range of 2,0-2,3 mmol O 2 /kg fat. The relatively low value of Pv (Pv 5 2.0 mmol O 2 /kg fat) for cocoa butter extracted from microwave roasted beans can be caused by a different method of heating the bean, short process time (t 5 12.5 min), and similarly as in roasting at T 5 140°C, the presence of antioxidant substances in the cocoa butter.…”
Section: Influence Of the Roasting Methods On Cocoa Butter Propertiesmentioning
confidence: 96%
See 3 more Smart Citations